THE PAPUAN HIGH SCHOOL STUDENTS’ PERCEPTION AND ATTITUDE TOWARDS ENGLISH MAJORS - Nurteteng, Nurteteng; Setiawan, Agus; Putri, Ferla Yulia Kamandani (Universitas Muhammadiyah Makassar, 2024)
The existence of English major in Southwest Papua is still become a big project for universities in improving the number of students to choose English major. Year by year, the new students who take this major is decreased. This is become the big reason to conduct this research that aims to discover the Papuan high school students' perceptions and attitudes towards English majors. The case study design was used to describe this case. This research involved five schools in Sorong and Raja Ampat Regency. The sample of this research was 50 Papuan high school students’ taken from the five schools that participated. In collecting the data, the research used interviews and attitude questionnaires. The result regarding the students' perceptions is that most Papuan students think English is confusing and complex. It is because of the teaching method or strategy that the teacher considers monotone and boring. The pedagogical competence of an English teacher also influences this student's opinion. As an impact, fewer want to pursue English-related careers, like educators or tourism jobs. Most want to become civil servants after graduating from senior high school. Regarding the student's attitude, 86% of respondents have a negative attitude towards the English major. The significant cause is that they previously had no interest or motivation in learning English. As an impact, most of them do not want to choose English as their major at the university level.